Eu, criador de mim: a criação do eu em um mundo de câmeras baratas, ilhas de edição acessíveis e sistemas de difusão democráticos - Godefroid, Ana Carolina (2017)
The possibility of ordinary people being able to produce and share videos, results in a significant expansion of the audio visual content, due to the digitalization of tools and platforms of communication. The exponential growth of amateur videos posted and shared on Youtube is the starting point of this reflection: Understanding the representation of one's "Self" and the production, such as the distribution system that, consequently, it demands. Everyday moments can become special. As has been witnessed a long the history of photography, and the magical relation people build with their photographs. This way, what was at first a simple documentation, becomes a performance in a perpetual motion that feeds off it's own re-interpretation, transforming this documentation in to content that completes, interacts, and sometimes transforms it's reality. The issue is: what are the chosen references and how do these types of productions reproduce the living or shared realities? And is there a difference between them? In this context the "Self" emerges as a representation, but also opens the possibility of transforming into an actor. Loosing it's personal characteristics. This way, the practice of video's representation, appropriation, recreation and sharing is audio visual language shifts with new network technology, creating formats that dialogue with documentary, but also changes its premisses. How do these new technologies enable most people to become audio visual producers and, most importantly, producers pf their own "Selfs"